RIGHT ISSUE: HUTANG ATAU INVESTASI? - Deny Dwi Hartomo (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2014)
The objective of this study is to examine the difference of investor reaction on rights issue announcement pursuant to the purpose of using fund in Indonesia capital market. Investor react positively if the most using fund of right issue for investment and investor react negatively if the most using fund of right issue for debt payment. This study also examine influence offering price of right issue to investor reaction.The samples are 55 firms that listing the rights issues in Indonesia Stock Exchange. Event study with 21 event window (from day -10 to day +10) are used to investigate the investor's reaction. Investor reaction is proxyed by abnormal return that was calculated by market-adjusted model. To investigate the determinants in investor's reactions are used linier regression between cumulative abnormal return for several days (determined based on significant abnormal return) as dependent variable and the purpose of using fund with dummy and offering price as independent variables.The conclusions of this study are: (1) investor react to right issue announcement, proved by significant abnormal return around right issue announcement date; (2) investor react positively to right issue announcement that mostly using fund for investment; (3) investor react negatively to right issue announcement that mostly using fund for debt payment; (4) offering price of right issue have positively influential to investor reaction.